Peningkatan Hasil Belajar Matematika Melalui Model Discovery Learning Berbantuan PPT Interaktif Pada Materi Peluang - Tungga, Chintya Julita Putri; Ekowati, Christine Krisnandari; Samo, Damianus D. (Fraktal : Jurnal Matematika dan Pendidikan Matematika, 2025)
This research was motivated by the mathematics learning results of class VIII students at SMP Negeri 1 East Kupang, especially regarding the material on systems of linear equations in two variables which was still low. The aim of this research is to improve the learning outcomes of class VIII students at SMP Negeri 1 East Kupang on two-variable linear equation systems.The type of research used is Classroom Action Research (PTK) which refers to a modelKemmis & Mc Taggart, which was carried out in 2 cycles with each cycle consisting of 4 stages, namely: 1) planning; 2) implementation; 3) observation; and 4) reflection. Data collection techniques in research are observation and tests, while data analysis is descriptive qualitative and quantitative.The results of this research show that the percentage of classical student learning completeness in cycle I was 66.67%, increasing to 80.95% in cycle II, the value of implementing observations of teacher teaching activities in cycle I and cycle II was 100%, and the value of implementing student activities in cycle I it was 84% ​​increasing to 100% in cycle II. Thus it can be concluded that the application of the modeldiscovery learningwith the help of powtoon animation videos, it can improve the learning outcomes of class VIII students at SMP Negeri 1 East Kupang on the material of systems of linear equations in two variables.